Peran Basis Data Dalam Kesuksesan Operasional Perusahaan Studi Kasus : PT Tokopedia - Haura Rifqa Hascarjani; Yohana Tirta Widia Swari Simamora; Khariunisa Harahap (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2025)
This study aims to examine the role of databases in supporting the operational success of PT Tokopedia. The theoretical basis refers to the concepts of databases, management information systems, competitive advantage theory, as well as big data and data-driven decision-making. The methodology used is a descriptive qualitative approach through literature study and secondary data analysis. The research findings indicate that databases play a key role in Tokopedia's operations, particularly in the real-time management of transactions, users, products, payment systems, and logistics. The success of database management is determined by aspects of scalability, security, system integration, high availability, and the utilization of big data and artificial intelligence. The implication is that databases are not only able to improve operational efficiency through automated and fast processes, but also strengthen service quality by providing a safe, personalized, and reliable shopping experience.